Negative interest rates, COVID-19, and the finances of listed euro firms - Johan H. von Eije (The Central European Review of Economics and Management (CEREM), 2021)
Aim: The paper measures the impact of negative interest rates on listed firms in the original euro zone countries. It also measures the impact of the first COVID-19 year. Design / research methods: The paper uses panel data to measure the influence of the short-term ECB deposit rate and the 10-years German bond yield on short-term and long-term firm variables. Cross section fixed effects are applied to first differences and dummy variables. For liquidity and non-liquid assets the effects are also measured for small and large companies, for sectors, and for countries. Conclusions / findings: Corporate liquidity ratios and creditor ratios decline when short-term ECB-rates fall. If ECB rates are negative, liquidity ratios are further reduced by 0.6 percentage points. Declining long-term German government bond yields increase non-liquid assets, while negative yields boost these assets by 4.5% extra. In the first COVID-19 year, the investments in non-liquid assets were 7.6% smaller, while liquidity ratios increased by 2.3 percentage points. Originality / value of the article: Papers on the influence of negative interest rates and of COVID-19 on European firms are unavailable. This makes the paper relevant for firm managers and policy makers and a benchmark for future research. Implications of the research: Because the issues addressed are new, further research is valuable. One may think of comparable studies for different countries. Many other suggestions for further research are given in the conclusions.
Keywords: E22; E31; E32; E58; G31; G35; 330; Negative interest rates; European Central Bank; German government bond yields; short-term firm financing; liquidity ratios; debtor ratios; creditor ratios; dividends; long-term borrowing cash flows; non-liquid investments; corona crisis; COVID-19